Reversal of GABA-mediated Inhibition of the Electrically and Potassium Chloride Evoked [3H]-GABA Release from Rat Substantia Nigra Slices by DL-3-Hydroxy-3-Phenyl Pentanamide - Meza-Toledo, Sergio E; Bowery, Norman G (Arzneimittelforschung, 2008)
The phenyl alcohol amides, DL-2-hydroxy-2-phenyl butyramide (CAS 52839-87-9), DL-3-hydroxy-3-phenyl pentanamide (CAS 131802-69-2, DL-HEPP) and DL-4-hydroxy-4-phenyl hexanamide (CAS 67880-30-2) and their fluorine and chlorine analogs, at a concentration of 100 µmol/L, did not displace [3H]-γ-aminobutyric acid ([3H]-GABA, CAS 108158-36-7) from GABAA receptors and only weakly displaced [3H]-GABA and [3H]-CGP62349 (CAS 186986-97-0), a GABAB receptor antagonist, from GABAB receptors in rat brain crude synaptic membranes. The electrically and potassium chloride (15 mmol/L) evoked [3H]-GABA release in the presence of DL-HEPP, GABA and GABAB receptor ligands from rat brain substantia nigra (SN) slices was studied. R-Baclofen (CAS 69308-37-8) (10 µmol/L), a GABAB receptor agonist, produced an inhibition of the electrically evoked [3H]-GABA release and this inhibition was blocked by CGP 55845A (CAS 149184-22-5) (10 µmol/L), a GABAB receptor antagonist, but was not affected by DL-HEPP (100 µmol/L). CGP 55845A (10 µmol/L) did not alter the electrically evoked [3H]-GABA release in the absence of baclofen. The addition of DL-HEPP (100 µmol/L) alone did not affect the electrically-evoked release of [3H]-GABA release control, but it was able to significantly reduce the inhibitory effect of GABA (CAS 56-12-2) (10 µmol/L) on [3H]-GABA release evoked both by electrical and potassium chloride stimulation, in the presence of tiagabine (CAS 115103-54-3) (10 µmol/L), a GABA uptake blocker. In three preliminary experiments, bicuculline (CAS 485-49-4) (10 µmol/L) and picrotoxinin (CAS 17617-45-7) (10 µmol/L), two GABAA antagonists, inhibited the electrically evoked release of [3H]-GABA from rat SN slices, and DL-HEPP (100 µmol/L) reversed this inhibition. The mechanism of action of DL-HEPP is not known but, it might act as a negative GABA modulator in rat brain slices.
Keywords: Anticonvulsants; GABA modulators, negative; DL-3-Hydroxy-3-phenyl pentanamide, influence on GABA binding; Substantia nigra, evoked [3H]-GABA release